2023
DOI: 10.1097/ogx.0000000000001110
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Approaches to Labor Induction

Abstract: Importance: The induction rate continues to increase in the United States placing pressure on the health care system with increasing cost and time spent on labor and delivery. Most labor induction regimens have evaluated uncomplicated singleton-term gestations. Unfortunately, the optimal labor regimens of medically complicated pregnancies have not been well described.Objective: The aim of this study was to review the current available evidence regarding the various labor induction regimens and understand the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The incidence of preterm births was higher in older patients as compared to young patients. Alexander put forth the preterm birth as one of the many adverse pregnancy outcomes which are associated with females of advanced maternal age (19). In our study it was found out that 22(15.2%) of the women in advanced age group had preterm births.…”
Section: Discussionmentioning
confidence: 54%
“…The incidence of preterm births was higher in older patients as compared to young patients. Alexander put forth the preterm birth as one of the many adverse pregnancy outcomes which are associated with females of advanced maternal age (19). In our study it was found out that 22(15.2%) of the women in advanced age group had preterm births.…”
Section: Discussionmentioning
confidence: 54%